1993
DOI: 10.1002/etc.5620120107
|View full text |Cite
|
Sign up to set email alerts
|

The aqueous photolysis of triclopyr

Abstract: The aqueous photolysis of triclopyr was examined in both pH 7‐buffered water and natural river water under artificial lights and midsummer sunlight (40°N latitude). The pseudo‐first‐order half‐lives in pH 7‐buffered water and natural river water averaged 0.5 and 1.3 d, respectively, at 25°C. Diffuse mercury lamps and midsummer sunlight produced similar rates of triclopyr decay and photoproduct distribution for a given solution. The photolysis of untreated river water produced a significantly different distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Such poor removals, at similar herbicide and ozone concentrations, are comparable to those reported for atrazine (Foster et al, 1992;Xiong and Graham, 19921. However, imazapyr and triclopyr both have lower affinities for particulate interactions and much greater solubilities than either atrazine or simazine (Neary et al ., 1993). Consequently, although the photodegradation rates of both imazapyr and triclopyr are reported to be rapid (Woodburn et al, 1993;Mallipudi et al ., 19911, if they are applied as replacements for the triazines, the potential of imazapyr and triclopyr to contaminate potable water supplies might be significantly greater.…”
Section: Discussionmentioning
confidence: 90%
“…Such poor removals, at similar herbicide and ozone concentrations, are comparable to those reported for atrazine (Foster et al, 1992;Xiong and Graham, 19921. However, imazapyr and triclopyr both have lower affinities for particulate interactions and much greater solubilities than either atrazine or simazine (Neary et al ., 1993). Consequently, although the photodegradation rates of both imazapyr and triclopyr are reported to be rapid (Woodburn et al, 1993;Mallipudi et al ., 19911, if they are applied as replacements for the triazines, the potential of imazapyr and triclopyr to contaminate potable water supplies might be significantly greater.…”
Section: Discussionmentioning
confidence: 90%
“…There are two reports regarding photodegradation pathways of chlorinated pyridines; they suggest the occurrence of hydrolytic dechlorination. Smith [1] speculated that TCP undergoes photodehalogenation with the formation of a series of diols, triols, and tetraols; Woodburn et al [14] reported that aqueous photolysis of the herbicide triclopyr (pH 7) produced 5‐chloro‐3, 6‐dihydroxy‐2‐pyridinyloxyacetic acid as the major product and other low‐molecular‐weight acids.…”
Section: Discussionmentioning
confidence: 99%
“…(1)) oxidize further the products of TCP oxidation. A number of studies on photocatalytic degradation of related chloromethylphenoxy herbicides, chloropyridines [56,57], and their derivatives including triclopyr [58][59][60] and clopyralid [61] revealed that the electrophilic attack of HO on the pyridine ring may lead to release of the chloride [56,60] and/or to formation of hydroxypyridines, and further to quinonic and ketonic structures [39,57], or even to ring opening [39]. Electrochemical incineration of chloromethylphenoxy herbicides using anodic oxidation at BDD anode by means of HO leads to formation of corresponding phenol derivatives and their further hydroxylation with benzoquinones as byproducts of HO iniciated oxidation [39].…”
Section: Mechanism Of Tcp Oxidationmentioning
confidence: 99%